Willingness to pay for green energy sources in the United Arab Emirates (UAE) - Haileslasie Tadele; Baliira Kalyebara (International Journal of Renewable Energy Development, 2023)
This study investigates the willingness of customers in the UAE to pay a premium for green energy (GE) sources. Given the huge initial investment required for GE projects, raising capital is often achieved by increasing energy bills or taxes. To explore this issue, the study surveyed 192 small and medium-sized businesses using the contingent valuation method. The results indicate that while most businesses are aware of solar and wind energy sources and the importance of combating climate change, half of them are not willing to compromise their current energy use and do not support an increase in utility bills or taxes to finance GE projects. However, older businesses tend to be more willing to pay a premium for GE compared to younger businesses. Overall, majority of the businesses support a voluntary increase in electricity bills. The findings highlight the crucial role of current electricity bills and knowledge about GE sources in shaping customers' willingness to pay. This study contributes to the literature on energy finance and the contingent valuation method in the context of green energy in the UAE.